DAKWAH BI AL-LISĀN DENGAN TEKNIK HIBURAN DI KOTA BANDA ACEH - Sukardi Sukardi (Islam Futura, 2014)
Da'wah is communication activitis in which the dai convey the messages to themaudu’i both personally and in group, how to express hte hidden behaviour of the humanbeing, it is clear must be putforward methof or tehnique to convey or to deliver messages correctly. The result of the study show that most of audienswellcome positively on the neccesity to have humor and gag in delevering the da’wa in order the listener are not bored in listening the conveying messages and the da’wa is interesting to be listened. Da'wah bi al lisan throught the intertaining tehnique prevalent nowadays according to ust in Banda Aceh is that generally the dai entertain the listener in da’wa is to make the listener interested in without eleminating the substance of the da’wa. The posistive impact of the da’wa bi al lisan throught the entertaining tehnique is that all the listener are motivated to listen to the da’wa. Besides, the listener not only listen for themselves but also bering any impact to their family to come together to listen to the da’wa.